Komunikasi Politik GAM-RI pada Perundingan Helsinki - Maulana, Reza (Jurnal Studi Komunikasi, 2018)
This study purposes to find out how political communication that occurs between GAM-RI negotiation in Helsinki on 2005. Helsinki negotiation is a phenomenon of political communication which is reached an agreement. The theory used is empathy and homophile. The research method uses a qualitative approach with descriptive research. Data collection tools in this study of semi-structured interviews and documentation study. Informant selection technique used is purposive technique. Based on the results of data processing in an interactive, results are obtained that negotiation built through six stages: preparation; The first contact; confrontation; conciliation; solutions; and post-negotiation. In the negotiations the two sides have similarities that can make both sides mutual trust and the creation of an effective political communication. The similarities among ethnic and organizational background. Effective use of empathy and homophile greatly affect the process and outcome of the negotiations.